A Cultural-Historical Activity Theory (CHAT) Analysis on Educational Psychology Class: The Challenges in Delivering a Fully Online Classroom Environment - Erina Andriani; Aletheia Ajeng Priskananda; Markus Budiraharjo (Journal of Foreign Language Teaching and Learning, 2022)
In assisting students’ transformation, classes provide activities with face validity. This paper aims to provide readers with cultural-historical activity theory (CHAT) analysis of Educational Psychology class at a private university in Yogyakarta. Activity Theory is a theoretical framework for the study and interpretation of human interaction through the use of instruments and objects. It provides a holistic and contextual discovery approach that can be used to help qualitative and interpretive research. Activity Theory is especially important in circumstances that have a large historical and cultural context and where participants, their goals and their tools are in a state of rapid and continuous change. Few studies explored the use of CHAT framework to reveal the challenges in providing a fully online class in a higher education. Therefore, this study intended to explore the practical importance of CHAT theory use for the delivery of a class in a fully online learning environment. The results revealed the units of analysis (UoA) of the CHAT framework. In addition, the students shared some challenges they faced in relation to those units of analysis. The implication of this study is to utilize the CHAT framework as a tool to evaluate the learning process.